(untitled) (Ghana Journal of Science, Technology and Development, 2022)
The objective of this study was to develop cowpea lines and assess them for drought tolerance using the pot screening approach. F1 lines were developed between September and November 2019 at University for Development Studies’ plant house. The drought experiment was conducted between February to March 2020. The F1 lines were developed by an artificial hybridization between the genotype ITK93-503-1 used as a male parent, obtained from the International Institute of Tropical Agriculture. This was crossed to 4 local genotypes used as female parents. The populations raised from the crosses were used to conduct the drought experiment. The experiment was Complete Randomized Design in; a 2 * 5 factorial experiment with 10 experimental units replicated three times, giving a total of 30 experimental units. The factors were; AbF1, GoF1, MF1, SaF1, ITK93-503-1 by Stress and Non-stress conditions. Plants were subjected to water stress for a period of 25 days and various drought related parameters were measured and analyzed. Results showed that water stress significantly (P<0.05) affected the chlorophyll content, leaf area and stem lodging for all F1 lines, however, water stress did not significantly (P>0.05) affect relative leaf water content of the F1 lines. The study showed that F1 lines (AbF1 and GoF1) performed better in chlorophyll content, leaf area, seedling recovery rate and plant main stem lodging. SaF1 recorded the highest relative leaf water content. Identified lines with drought tolerance potential should be further evaluated in subsequent generations to confirm their tolerance to drought for further selection and improvement.